ITALIAN MINORITY IN ISTRIA: DEVELOPMENT IN CJNDITIONS OF MULTICULTURAL AND MULTI-ETNIC SOCIETY - A. Marash (Vestnik MGIMO-Universiteta)
The article identifies and discloses the problems of national minorities living on the territory of the Istrian peninsula with access to the Adriatic Sea and the region Venezia Giulia. It must be stressed that the population of Istria just over the past century four times "changed citizenship", having been in the Austro-Hungarian Empire, the Kingdom of Italy, Federal People's Republic of Yugoslavia- FPRY (later - the Socialist Federal Republic of Yugoslavia - SFRY), and, finally, the People`s and the Socialist Republic of Croatia. It is shown that all of these political changes in different periods strongly influenced mentality of the population, especially in matters relating to the treatment of national minorities. Consequently, the composite structure of the population of Istria and Venezia Giulia with time has undergone profound changes: Latinized ethnolinguistic group assimilated by Slavic population, but subsequently was different from the Slovenes and Croats. Before the First World War, these territories were part of the Austro-Hungarian Empire, and there lived the Italians, Croats and Slovenes. After the war and the collapse of the empire the region became part of the Kingdom of Italy. New problems arose at the end of the Second World War, when most of the Istria and Venezia Giulia was under the control of the newly established Democratic Federal Yugoslavia. As a result, after the break-up of the federation of Yugoslavia and the formation of autonomous and independent states - former republics including Croatia, the status of national minorities have separate national and cultural groups, where Italians as an autochthonous national minorities enjoyed the status of the privileged minority.